Invasive fungal disease in COVID-19 patients: a single-center prospective observational study - Adzic-Vukicevic, Tatjana; Mladenovic, Milos; Jovanovic, Snezana; Soldatović, Ivan; Radovanovic-Spurnic, Aleksandra (Frontiers in Medicine, 2023)
Introduction Invasive fungal disease (IFD) represents serious secondary infection in patients with COVID-19. The excess morbidity and mortality rate is most frequently observed in COVID-19-associated pulmonary aspergillosis (CAPA) and COVID-19 associated candidiasis (CAC). CAPA was most frequently documented with an incidence rate of 0.7%-7.7%, while CAC is less common and less studied fungal infection in COVID-19 patients. Material and methods A prospective observational single center study among 6335 patients admitted to Covid Hospital Batajnica, University Clinical Centre of Serbia, Belgrade, has been performed from 1st September 2021 to 24th December 2021. Results The study included 120 patients (1.86%) out of 6335 hospitalized in the fourth month’s period with proven diagnosis of IFD. Patients were divided into two groups, CAPA (n=63) and CAC patients (n=56), while one had Cryptoccocus neoformans infection. The mean age was 65.7±13.9 years and 78 (65.5%) were male. Non-malignant comorbidities included arterial hypertension in 62 (52.1%) patients, diabetes mellitus in 34 (28.65), pre-existing lung damage like in COPD and asthma in 20 (16.8%) and chronic renal insufficiency in 13 (10.9%) patients. Among malignancies hematological ones were prevalent in 20 (16.8%) patients, especially in CAPA patients 11(17.5%) (p<0.041). Fiberoptic bronchoscopy with (bronchoalveolar lavage fluid) BALF and microscopic confirmation were performed in 17 (14.3%) patients. Serology testing was performed in the majority of cases including Aspergillus spp and Candida spp antibodies dominantly positive in CAPA patients (p<0.001), as well as (1-3)-β-D glucan (p<0.019), galactomannan and mannan testing. Positive blood cultures were found in 45 (37.8%) patients, mostly in CAC patients. Mechanical ventilation was applied in 41(34.5%) patients while non-invasive including continuous positive airway pressure (CPAP) or high flow nasal carine (HFNC) was used in 20(16.8%) patients. Of antifungals were used echinocandins in 42 (35.3%), voriconazole in 30 (25.2%), and fluconazole in 27 (22.7%) patients. Overall, all the patients received systemic corticosteroids (mainly methylprednisolone), 11(9.16%) favipiravir, 32(26.67%) remdesivir, eight (6.67%) casirivimab/imdevimab and five (4.16%) sotrovimab. Lethal outcome occured in 76(63.9%) patients, dominantly in CAC patients (p< 0.001). Conslusion IFD represents a severe complication of COVID-19 associated with increased mortality. Prompt recognition and treatment may lead to a favorable outcome.